The Role of Islamic Religious Education in 21st Century Science and Technology - Wantu, Hasyim Mahmud; Intes, Amina; Barroso, Uwe; siyono, Siyono (Yayasan Pendidikan Islam Daarut Thufulah, 2024)
Background. Today's science and technology play an important role in education. However, it resulted in many changes in the social and moral order. Students are required to catch up and master increasingly sophisticated science and technology. So the process of forgetting religious and moral values because they are considered ancient, stylish things are considered advanced and modern. The influence of advances in science and technology can be countered by means of education, especially Islamic Religious Education. Purpose. The role of Islamic Religious Education helps to restore morals and ethics in the pursuit of science and technology. This role is explained in the Koran that humans are created with eyes to see, ears to hear and hearts to consider what is pursued in gaining knowledge. The aim of this research is to determine the role of Islamic Religious Education on science and technology. Method. This research involves students to get the desired results. The method used in the research is a quantitative method by distributing questionnaires to students via Google Form Results. The research results show that the role of Islamic religious education in science and technology has a big influence on the educational process. Conclusion. The conclusion from the research is that the role of Islamic Religious Education must be increased further in following developments in science and technology. Therefore, the limitation of the research is that the researcher did not undertake to look at the role of Islamic Religious Education in the world of science and technology in the 21st century. The researcher hopes that future researchers will carry out the same research in order to obtain in-depth and comprehensive research results so that the results are maximum.